2019
DOI: 10.1371/journal.pone.0225849
|View full text |Cite
|
Sign up to set email alerts
|

Total sleep deprivation increases pain sensitivity, impairs conditioned pain modulation and facilitates temporal summation of pain in healthy participants

Abstract: Chronic pain patients often suffer from insomnia or impaired sleep which has been associated with increased pain sensitivity, but a limited amount of studies have investigated the effects of total sleep deprivation on central pain mechanisms. Therefore, the aim of this study was to determine the effects of total sleep deprivation on temporal summation, conditioned pain modulation, thermal and pressure pain sensitivity in healthy participants. Twenty-four healthy participants took part in this two-session trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 67 publications
(92 reference statements)
3
80
2
Order By: Relevance
“…A widely accepted view in the scientific community is that sleep deprivation decreases pain tolerance and increases the transmission of pain in multiple chronic pain conditions [ 160 , 161 , 162 , 163 , 164 , 165 ]. There is a conflict between reports on the sensory perception of pain [ 166 , 167 ], which was negatively affected in our study ( Figure 3 B), and few studies indicated that only total sleep deprivation raises the intensity of pain rather than REM sleep deprivation [ 168 , 169 ]. Nonetheless, selective REM sleep deprivation is correlated with enhanced placebo analgesia effects [ 170 ].…”
Section: Discussioncontrasting
confidence: 87%
“…A widely accepted view in the scientific community is that sleep deprivation decreases pain tolerance and increases the transmission of pain in multiple chronic pain conditions [ 160 , 161 , 162 , 163 , 164 , 165 ]. There is a conflict between reports on the sensory perception of pain [ 166 , 167 ], which was negatively affected in our study ( Figure 3 B), and few studies indicated that only total sleep deprivation raises the intensity of pain rather than REM sleep deprivation [ 168 , 169 ]. Nonetheless, selective REM sleep deprivation is correlated with enhanced placebo analgesia effects [ 170 ].…”
Section: Discussioncontrasting
confidence: 87%
“…A widely accepted view in the scientific community is that sleep deprivation decreases pain tolerance and increases the transmission of pain in multiple chronic pain conditions [158163]. There is a conflict between reports on the sensory perception of pain [164,165] which was negatively affected in our study ( Fig. 3B ) and few studies indicated only total sleep deprivation raises the intensity of pain rather than REM sleep deprivation [166,167].…”
Section: Discussioncontrasting
confidence: 60%
“…The present findings should be carefully interpreted in terms of the methodological limitation. Despite the theoretical backgrounds of unidirectional effect of disturbed sleep causing pain, 48,50,51 our cross‐sectional design prevents the causal relationships between sleep and pain. The conceptual hypothesis of mediation analysis in this study is that sleep may predict jaw functional limitation via pain.…”
Section: Discussionmentioning
confidence: 99%